Effect of Cu\(^{2+}\) Dopant on the Formation of Zinc Oxide Microrod Fabricated by a Hydrothermal Method - Nguyen, Sang Xuan; Le, Phuoc Sang; Luu, Thi Lan Anh (Communications in Physics, 2022)
Reconstruction and stabilization of polar oxide surfaces, such as ZnO, contribute a significant role in photocatalysis, chemical sensing, and optoelectronic applications, however their physical chemistry insight is still a puzzle in the surface science. In this work, the  polar surface instability induced the morphological evolution of hydrothermally synthesized micro-rod ZnO doped with various contents of Cu2+ ion (1-10 at.%)  was investigated. The transformation of micro-rod morphology from the high aspect ratio flower-like shape of the pure ZnO to the hexagonal prism-like shape of the doped ZnO was characterized by X-ray diffractometry, scanning electron microscopy and micro Raman spectroscopy. The chemically active Zn-terminated polar surface in doped samples was less positive charge density which was the main reason to cancel the electrostatic instability for the dominant  growing direction. Furthermore, the schematic models of the electron transferring from the conduction band region to the electron trap centre of Cu2+, and the Zn-terminated polar surface reconstruction were proposed for the morphological evolution mechanism.